Darwin’s prescient letter regarding orchid mycorrhiza - Arditti, Joseph (2025)
On March 26, 1863, Charles Darwin wrote a letter to Joseph Dalton Hooker, describing his attempts to germinate orchid seeds. In this letter, he mentioned his hope to observe orchid seedlings and expressed a “notion that [the seeds]. . . are parasites in early youth on cryptogams!!”. This statement appears to predict Noël Bernard’s 1899 discovery that orchid seeds require fungal colonization for successful germination. However, there is some uncertainty regarding Darwin’s exact meaning. The term “cryptogams” in his time commonly included fungi but also encompassed bryophytes, pteridophytes, and other non-vascular plants. Since Darwin mentioned sphagnum in his experiments, it is possible to suggest that he may have considered mosses as potential hosts rather than fungi. But, since this was a personal letter to Joseph D. Hooker rather than a formal publication, Darwin may have been less precise in his terminology. Nevertheless, considering Darwin’s broader interest in plant-fungal interactions, it is very plausible that he regarded fungi as possible symbiotic partners in orchid germination. The extent of Darwin’s prescience on the orchid-fungal relationship may be debatable terminologically (did he mean fungi by using “cryptogams”?). However, his speculation was remarkably intuitive, questioning whether orchids required an external biological partner for germination. Darwin’s letter demonstrates his foresight, but it does not diminish Noël Bernard’s monumental achievement. Bernard made his discovery independently, without knowledge of Darwin’s observations, relying solely on his extraordinary scientific talent. His work remains a cornerstone of orchid science. Unfortunately, Darwin’s prescient letter seems not to have been noticed, appreciated, or cited often enough in the orchid literature during its 162 years of existence.